The combined effects of napping and self-selected motivation music during warming up on cognitive and physical performance of karate athletes - Bentouati, Emna; Romdhani, Mohamed; Abid, Rihab; Khemila, Syrine; Garbarino, Sergio; Souissi, Nizar (Frontiers in Physiology, 2023)
Introduction: It has been established that napping or listening to motivational music during warmup are an effective strategy to enhance cognitive and physical performances. However, which could provide better enhancement warrants more investigations. This study aimed to examine the effect of a 30min nap opportunity (N30), a warm-up with self-selected motivational music (WUMM) and the combination of N30 with WUMM (WUMM+N30) on cognitive and physical performances in karate athletes.Method: In a randomized order, fourteen national-level male karate athletes performed four experimental sessions; control, N30, WUMM and WUMM+N30. Simple (SRT) and choice (CRT) reaction times, selective attention, subjective sleepiness (ESS), mood state (POMS), counter movement jump (CMJ) and karate agility test (KAT) were evaluated before and after an all-out exhaustive task [i.e., the karate-specific test (KST)]. Ratings of perceived exertion (RPE) were measured immediately after KST.Results: Compared to control, all interventions improved cognitive outcomes, mood and sleepiness. No effects on physical performances (CMJ, KAT) after N30 were found. Compared to N30, d=0.72; post: p<0.001, d=0.14), CRT (pre: p<0.001, d=0.07; post: p<0.001, d=0.10), attention (pre: p<0.05, d=0.06; post: p<0.01, d=0.06), mood (pre: p<0.001, d=2.53; post: p<0.001, d=0.23) and decreased ESS scores (pre: p<0.01, d=1.41; post: p<0.05, d=1.18). However, there was no significant difference between WUMM and N30. KST performance was not affected by the experimental conditions. However, the KST-induced performance deficit in CMJ and KAT was smaller following WUMM+N30 compared to WUMM and N30. RPE scores were lower following WUMM+N30 and WUMM.These findings suggest that a combination of listening to self-selected motivational music during warm-up with a 30 min nap could be an effective strategy to enhance cognitive and physical performances decline caused by fatigue induced by the exercise.